2020
DOI: 10.1002/lio2.365
|View full text |Cite
|
Sign up to set email alerts
|

Effect of relevant factors on radiation‐induced nasopharyngeal ulcer in patients with primary nasopharyngeal carcinoma treated with intensity‐modulated radiation therapy

Abstract: Objective: To analyze the correlation between relevant factors and radiation-induced nasopharyngeal ulcer (RINU) in primary nasopharyngeal carcinoma (NPC) treated with intensity-modulated radiation therapy (IMRT).Methods: Clinical data were collected for 599 patients with newly diagnosed NPC who had completed IMRT. The entire cohort was randomly divided into two subgroups. The relationship between RINU and IMRT dose-volume were statistically analyzed with ROC curves and the Chi-square test. Nutritional status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The crude incidence rate of INN was 1-2.9% among the NPC population [11,12,14], and 3.3% in patients treated with IMRT while 2.3% with 2D radiotherapy [11]. Compared to 2D radiation therapy, IMRT enables target volumes to receive higher doses, which may increase the incidence of INN.…”
Section: Association Between Treatment Strategies and Innmentioning
confidence: 99%
See 1 more Smart Citation
“…The crude incidence rate of INN was 1-2.9% among the NPC population [11,12,14], and 3.3% in patients treated with IMRT while 2.3% with 2D radiotherapy [11]. Compared to 2D radiation therapy, IMRT enables target volumes to receive higher doses, which may increase the incidence of INN.…”
Section: Association Between Treatment Strategies and Innmentioning
confidence: 99%
“…Quite a few studies have been reported risk factors to predict INN. The accumulated total dose of radiation, malnutrition, and infection are generally recognized as predictive factors [7,[10][11][12]. Yu developed a model including gender, pretreatment necrosis, accumulated total prescription dose, and recurrent tumor volume to predict INN in NPC patients with re-irradiation [13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we aimed to investigate whether the intensive treatment strategies would increase the risk of INN occurrence. A propensity-score matching methodology was used to balance other potential risk factors, such as T stage, gender, age, pathological type, biomarkers of nutritional status (hemoglobin, albumin, body mass index), and in ammation status (C-reactive protein, necrosis before re-irradiation), which were reported by published researches 11,12,13,17 . As a result, our study noted that adding chemotherapy or targeted therapy did not increase the risk of developing INN, as in line with other studies 11,23 .…”
Section: Clinical Feature and Prognosis Of Innmentioning
confidence: 99%
“…Quite a few studies have been reported risk factors to predict INN. The accumulated total dose of radiation, malnutrition, and infection are generally recognized as predictive factors 10,11,7,12 . Yu developed a model including gender, pretreatment necrosis, accumulated total prescription dose, and recurrent tumor volume to predict INN in NPC patients with re-irradiation 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation